EFFECT OF RITUXIMAB ON THE BLOOD CHOLESTEROL TRANSPORT SYSTEM IN PATIENTSWITH RHEUMATOID ARTHRITIS - Tatyana Valentinovna Popkova; D S Novikova; O G Lineva; A A Novikov; E N Aleksandrova; E L Nasonov (Научно-практическая ревматология, 2010)
Objective: To study the time course of changes in the indices of the blood lipid spectrum in patients with rheumatoid arthritis (RA) treated with rituximab during a 24-week follow-up. Subjects and methods. The study enrolled 39 patients (36 females and 3 males) with a valid diagnosis of RA; their mean age was 50 years; disease duration 93.5 months; duration activity scale (DAS) 6.1 scores. A previous ineffective treatment with methotrexate was found in 6 patients; that with two basic anti-inflammatory drugs or more in 30, and previous TNF- inhibitor therapy failed in 14 of the 39 patients. The blood lipid spectrum and intima-media thickness (IMT) were determined before and 24 weeks after the first injection of rituximab. The drug was intravenously administered dropwise in a dose of 1000 mg twice at a 14-week interval. Therapeutic efficiency was estimated according to the RA activity index - DAS28. All the patients showed a satisfactory/good response to rituximab therapy. Results. There was a double reduction in the frequency of hypoalfalipoproteinemia and in the increased atherogenicity index (AI). Elevated cholesterol (CH), triglycerides (TG), and low-density lipoprotein (LDL CH) levels were found in equal frequencies before and 24 week after rituximab administration. There was a 5% rise in CH concentrations, a considerable (22%) increase in high-density lipoprotein CH, and an 18.6% decrease in AI (p